Implementación de la metodología building information modeling en la gestión de proyectos inmobiliarios (2020)
Currently, the real estate project management is a complex action for doing because they have a lot process for develop across his life cycle, the lack of methodology, creation and definition for that process at the end they are the responsible for delays, re-process and over cost in relation with develop for the project. In that moment the building information modeling have an important role beyond to be a global tendency for his technology implementation, Its meaning an opportunity to allow a better optimization and more efficiency for all process involved in construction.